Unbiased, comprehensive analysis of Japanese health checkup data reveals a protective effect of light to moderate alcohol consumption on lung function - Kanako Makino (Nature Portfolio, 2021)
Abstract The overall effect of lifestyle habits, such as alcohol consumption, on general health remains controversial and it is important to clarify how such habits affect aging-related health impairments. To discover novel impacts of lifestyle on general health, we employed a mathematical approach to perform a comprehensive, unbiased, cross-sectional analysis of data from 6036 subjects who participated in a Japanese health checkup. Notably, we found that moderate alcohol consumption was positively correlated with lung function, muscle mass, and strength. Health checkup data were collected periodically from the same subjects. These people were light to moderate drinkers who had high health awareness and were basically free of major underlying diseases. We next analyzed 5 years of data from 1765 of these subjects. We found that higher baseline alcohol consumption, as well as increased alcohol intake over 5 years attenuated time-related deterioration of forced vital capacity without affecting total lung volume. This effect was independent of smoking. Our study suggests a possible protective effect of moderate amounts of alcohol on lung function, due to increased muscle mass/strength and forced vital capacity.